Implementasi PID Untuk Pengendalian Level Air Dua Tabung Paralel Pada Plant Labvolt Festo - Krisna Gunayanuar; Hadi Supriyanto; Muhammad Nursyam Rizal (JTRM (Jurnal Teknologi dan Rekayasa Manufaktur), 2025)
DCS Labvolt Festo is a tool as a learning media for water level control systems and water discharge flow using PID control. In this research, the DCS LabVolt Festo plant uses several different components and different controllers such as the Siemens S7-1200 PLC. The method in controlling the water level of two tubes in parallel is using PID control. Radar Level Transmitter and Differential Pressure Transmitter are used as feedback for Tube 1 and Tube 2. Then the application to display the interface that is uses Wonderware InTouch as the interface of all components in the plant. The integration between the DCS LabVolt Festo plant and the Wonderware Intouch application has been successful using OPC KEPServerEX while for the control of the water level in two tubes in parallel using PID with 100% and 50% valve interference gets a fairly stable response with overshoot below 10% for both tubes. For both tubes it is steady state but there are some setpoints that have a steady state error below 5%. To control two tubes, achieve simultaneous setpoint at the same time by adjusting the maximum motor frequency of Tube 2 with a smaller volume according to the setpoint used.